The elephant in the room - Sloan, Holly Goldberg, 1958- (New York : Dial Books for Young Readers, 2021)
Missing her mother who has returned to Turkey to resolve an immigration problem, sixth-grader Sila welcomes a very large distraction in her life when she helps a surprising new friend rescue a circus elephant.
School Library Journal starred, March 2021
Publishers Weekly, January 2021
Booklist, January 2021
Kirkus Review, February 2021
Library Media Connection, August 2021
4.8
Keywords: Friendship -- Juvenile fiction; Elephants -- Juvenile fiction; Separation (Psychology) -- Juvenile fiction; Emigration and immigration -- Juvenile fiction; Turkish Americans -- Juvenile fiction; Friendship -- Fiction; Elephants -- Fiction; Separation -- Fiction; Emigration and immigration -- Fiction; Turkish Americans -- Fiction